An Unstudied Compilation with the Name of Andrew the Apostle - Miltenova, Anissava (Studia Ceranea, 2014)
The paper presents an unstudied text with the name of the Apostle Andrew in the miscellany of 15th c., now Muz.10272, Rashka orthography. The text (with traces of archaic archetype) is a unique copy of the compilation. The history of the manuscript is very interesting, because it belonged to the A. Hilferding collection in the past. The aim of the author is to propose a preliminary analysis of the text, its origin and chronology, as well as its context in the Slavic tradition.